HOUSEHOLD HOUSE INCOME IN THE LAKE OF KAJUIK LANGGAM SUB DISTRICT PELALAWAN REGENCY RIAU PROVINCE - Titik Sartika; Firman Nugroho; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractThis research was conducted on February 2018 located at Kajuik Lake, Langgam Sub District, Pelalawan Regency, Riau Province. The location of this study is determined deliberately with the consideration that this location has a fisherman community in supporting the husband's economy assisted by members of the household. This study aims to find out Knowing the characteristics of fishermen, fishermen's wife and fishermen, Knowing the contribution of household members in the fishery sector or non-fishery sector to household income of fishermen and See the difference of income before and after the change of lake management from indigenous peoples to the government to income fishermen in Lake Kajuik. The method used in this study is the survey method with respondents amounted to 10 fishermen, where Determination of respondents is determined by the technique chosen purposely (purposive sampling). The characteristics of fisherman, fisherman's wife and fisherman's son in this study are: a) age, b) number of dependents c) work experience and d) level of education, contribution of household members, contribution contribution provided by fisherman is very high while contribution from wife is low and contribution from middle-aged children, and experienced income difference before and after management change from average of fisherman's income Rp 2,946,634 / month to Rp 1,396,634 / month or there is income difference Rp. 1.550.000 / month. The contribution of household members of fishermen of Kajuik lake are 48,31% fisherman, fisherman's wife 19,47% and fisherman's son 32,47%. Keywords: Household Income, Contributions, Lake Kajuik.